2020
DOI: 10.1021/acschemneuro.0c00294
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor (VEGF) as a Vital Target for Brain Inflammation during the COVID-19 Outbreak

Abstract: The coronavirus disease 19 (COVID-19) pandemic has brought a great threat to global public health. Currently, mounting evidence has shown the occurrence of neurological symptoms in patients with COVID-19. However, the detailed mechanism by which the SARS-CoV-2 attacks the brain is not well characterized. Recent investigations have revealed that a cytokine storm contributes to brain inflammation and subsequently triggers neurological manifestations during the COVID-19 outbreak. Targeting brain inflammation may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 6 publications
1
70
0
Order By: Relevance
“…Finally, increasing VEGF concentrations, which recruit inflammatory cells into the brain and sustain neuroinflammation, have been named as target for COVID-19 treatment [167]. The COVID-19 entry receptor ACE2 activates RAAS for neuroinflammation and VEGF synthesis by Ang II binding to AT 1 R (reviewed in ref.…”
Section: Neuropsychiatry and Neurodegenerative Disorders Associated Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, increasing VEGF concentrations, which recruit inflammatory cells into the brain and sustain neuroinflammation, have been named as target for COVID-19 treatment [167]. The COVID-19 entry receptor ACE2 activates RAAS for neuroinflammation and VEGF synthesis by Ang II binding to AT 1 R (reviewed in ref.…”
Section: Neuropsychiatry and Neurodegenerative Disorders Associated Tmentioning
confidence: 99%
“…The COVID-19 entry receptor ACE2 activates RAAS for neuroinflammation and VEGF synthesis by Ang II binding to AT 1 R (reviewed in ref. [167]). Besides ACE2, aberrant P2X7 receptor activation also induces VEGF release and signaling in the brain [168].…”
Section: Neuropsychiatry and Neurodegenerative Disorders Associated Tmentioning
confidence: 99%
“…As ACE2 is widely expressed on the epithelial cells of the oral mucosa, SARS‐CoV‐2 can breach the BNB accessing the CNS via the cranial nerve using axonal transport machinery (Zhou et al., 2020). The upregulated vascular endothelial growth factor VEGF (C and A) is associated with COVID‐19 endothelial barrier dysfunction (Ackermann et al., 2020; Yin et al., 2020), and specifically with the BNB (Lim et al., 2014). As VEGF is also related to angiopoietins (Ang I and Ang II), accumulation of Ang II facilitates the elevation of VEGF and inversely augments Ang II, which forms a vicious cycle in the release of inflammatory cytokines including TNF‐α, IL‐1β, IL‐6, IL‐8, and ICAM‐1, which causes BBB and BNSB disruption (Yin et al., 2020).…”
Section: Blood–nervous System Barriers (Bnsbs)mentioning
confidence: 99%
“…Numerous studies have confirmed a key role of VEGF-A as potential therapeutic target in ALI and ARDS due do the increased vascular permeability and pulmonary edema [258]. Furthermore, VEGF-A has been involved in disruption of the blood-brain barrier and may contribute to brain inflammation in the course of SARS-CoV-2 infection [259]. Thus, blockage of VEGF-A might have a role in COVID-19 management.…”
Section: Anti-vascular Endothelial Growth Factor-a (Vegf-a) Mabmentioning
confidence: 98%